Letters of the Motor Girl - Gardner, Ethellyn (Salt Lake City, UT : Project Gutenberg, 2011)
"Letters of the Motor Girl" by Ethellyn Gardner is a fictional work likely written in the early 20th century. The book is presented through a series of letters penned by the protagonist, Elsie, a spirited fourteen-year-old girl, who is enthusiastic about automobiles and explores various adventures with her family and friends. The narrative reflects her lively personality, fascination with modern technology, and her amusing insights about life. The opening of the novel introduces readers to Elsie's character on her fourteenth birthday. She expresses her joy in learning to drive her father's automobile, the Franklin Model G, and shares whimsical anecdotes about her family dynamics, her fondness for chocolates, and her interactions with her crush, Levey Cohen. Through her letters, Elsie illustrates her youthful exuberance as she recounts her experiences at a circus, her aspirations, and a hint of her unconventional ideas about society and gender roles. The letters convey a sense of humor and charm, setting the stage for a delightful exploration of a young girl's adventures in a rapidly changing world, where automobiles represent freedom and excitement. (This is an automatically generated summary.)
Release date is 2011-05-30
Produced by Roger Frank
Keywords: Epistolary fiction; Girls -- Fiction; Franklin automobile -- Fiction